Analisis Speech Delay Pada Gangguan Berbahasa Anak Selebriti Indonesia Dalam Tinjauan Kajian Psikolinguistik - Achmad Maulana Irchamna; Regina Maya Arisanti; Lisanur Azizah; Maria Mintowati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Speech delay is a condition of delayed development of speaking abilities in children who are below the normal developmental stage for their age. The phenomenon of speech delay in Indonesian celebrity children is interesting to study from a psycholinguistic perspective. Psycholinguistics is a branch of science that studies the relationship between language and the mental processes involved in language use and provides an in-depth understanding of the causes and treatment of speech delay in celebrity children. This research aims to analyze cases of speech delay in children of Indonesian celebrities in a review of psycholinguistic studies. The research method used is a literature study by collecting data related to speech delay and language disorders in Indonesian celebrity children through YouTube video shows and through article reviews. The results of the analysis show that speech delay in Indonesian celebrity children can be caused by neurological problems, genetic and environmental factors. A psycholinguistic perspective helps understand the mental processes involved in the acquisition and use of language in celebrity children who experience speech delay. Some treatment recommendations that can be given include speech therapy, communication stimulation, as well as family and social environmental support that is conducive to the child's language development.